2019
DOI: 10.21273/hortsci14025-19
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method to Track Changes of Candidatus Liberibacter asiaticus Titer in HLB-affected Citrus Trees

Abstract: Monitoring the health of Huanglongbing-affected citrus trees by following changes in leaf Candidatus Liberibacter asiaticus (CLas) titer has an inherent element of imprecision because CLas titer varies considerably within the tree canopy and with calendar seasons. In addition, the destructive sampling method used to determine CLas titer entails a different set of leaves per sampling period adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Samples of two leaves from each tree were taken at time 0 and 6 weeks after the treatment, for qPCR analysis of ‘ Ca . Liberibacter asiaticus’ using Applied Biosystems 7500 PCR instrument (Life Technologies, Carlsbad, CA, USA) as described earlier [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Samples of two leaves from each tree were taken at time 0 and 6 weeks after the treatment, for qPCR analysis of ‘ Ca . Liberibacter asiaticus’ using Applied Biosystems 7500 PCR instrument (Life Technologies, Carlsbad, CA, USA) as described earlier [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Here, lack of homogeneity impedes effective evaluations of treatments (especially those with low efficacy). Nonetheless, it has been reported that the use of multiple disks taken from the same leaf significantly reduces the random variability associated with C Las [ 57 ], and thus, this hindrance was addressed in our assay. Low initial infection rates are another hurdle in analyzing the efficacy of treatments, particularly due to the minimized effect potential.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred μL of each plant extract treatment (at 1%) and 0.5 mM streptomycin were added to their respective wells (7 replicates of each treatment per 96-well plate). To reduce variability associated with C Las, this assay used a cross-comparison of disks taken from the same leaf as a blocking factor [ 57 ]. Using a sterile biopsy punch, 4 mm leaf disks were punched along the midrib of each leaf, beginning from the base of the leaf and moving out.…”
Section: Methodsmentioning
confidence: 99%
“…Plant tissues were sampled monthly from the same 12 mature leaves on each replicate tree. Samples were collected by harvesting discs from these leaves beginning at the leaf tip and progressing down the petiole on each sampled leaf as described in [ 37 , 38 ]. Plant tissue samples were immediately flash frozen in liquid nitrogen, ground with a tissue lyser, and stored at − 80 °C for further analyses.…”
Section: Methodsmentioning
confidence: 99%